Nonlinear Dynamic Average Model of a DC-DC Converter - Busada, Claudio (2014)
A nonlinear dynamical average model of a dc-dc converter is presented. The converter under study has a particular feature. In this converter, classical average analysis cannot be applied because the ripple cannot be neglected in all state variables. For this reason, classical average analysis is not appropriated for obtaining an average model of the studied converter. In order to validate the introduced model, responses obtained by using the proposed average model and the commutated model are compared. The comparison is realized via simulation results.